Pedagogical Deep Learning for Student Character Formation: A Systematic Literature Review and Conceptual Synthesis - Nana Liesdiana; Mohammad Syaifuddin; Kusnaini (WISE Pendidikan Indonesia, 2026)
The growing emphasis on character-oriented education requires pedagogical approaches that move beyond knowledge transmission toward reflective, contextual, and value-laden learning experiences. This study aims to synthesize how deep learning approaches are conceptualized and implemented in education and how they contribute to student character formation. A Systematic Literature Review was conducted using PRISMA procedures. Articles were searched in the Scopus database on November 4, 2025, covering publications from 2016 to 2025 with the keywords “deep learning approach” and “character education.” After screening 4,244 initial records through title, abstract, document type, language, and eligibility criteria, 41 articles were included for thematic qualitative synthesis. The findings show that deep learning is implemented through diverse pedagogical models, including project-based learning, problem-based learning, contextual learning, flipped classroom, technology-supported media, reflective activities, and collaborative learning. Across the reviewed studies, deep learning supports character formation by promoting mindful engagement with content, meaningful connections to real-life contexts, and joyful learning experiences. These processes strengthen discipline, responsibility, independence, empathy, tolerance, collaboration, integrity, and critical thinking. This study contributes a conceptual synthesis that positions deep learning as an integrative pedagogical mechanism linking cognitive depth, reflective self-regulation, and character development, thereby offering a foundation for future empirical research and classroom-based innovation.